HELL IN IBN ʿARABĪ ACCORDING TO AL-SHAʿRĀNĪ - Abdul Muthalib (Peminat Ilmu Ushuluddin, 2022)
Ibn ʿArabī and his teachings were enormously influential and controversial in post-classical Islamic thought and Sufism. Attitudes towards his ideas ranged from sympathy and admiration to outrage and denunciation as disbelief. One major champion and interpreter of Ibn ʿArabī was the Egyptian Sufi ʿAbd al-Wahhāb al-Shaʿrānī, who believed that the Andalusian mystic was divinely inspired and an outstanding source for many religious sciences. Al-Shaʿrānī ‘s contribution to the Akbarian tradition has been largely neglected by modern scholars, who have tended to consider him a simplifier of Ibn ʿArabī’s teachings. This article aims to advance our knowledge of al-Shaʿrānī’s engagement with Ibn ʿArabī by examining his treatment of Ibn ʿArabī’s controversial belief that the heat and chastisement of hell will eventually terminate, even for Iblīs. It shows that al-Shaʿrānī’s tendency to stress Ibn ʿArabī’s orthodoxy while criticizing or avoiding some of his views and dissociating the Greatest Master from them, which he shared in part with the Shādhiliyya, is reflected in his engagement of this issue.